The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1007/s00595-004-2828-z
|View full text |Cite
|
Sign up to set email alerts
|

Screening Cost for Abdominal Aortic Aneurysms: Japan-Based Estimates

Abstract: Screening for AAA using ultrasound is useful not only for the early detection of AAA but also for a reduction in the overall medical cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…Of the 17 studies that were excluded after reviewing the full text, two did not meet the inclusion criteria as they had screened fewer than 1000 women: 795 women and 796 women. Three large studies were excluded: one consisted of a selected population (including 14 834 Chinese women with hypertension) and the other two had been carried out in 1992 and between 1992 and 1997 respectively. A recent French study provided insufficient information.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 17 studies that were excluded after reviewing the full text, two did not meet the inclusion criteria as they had screened fewer than 1000 women: 795 women and 796 women. Three large studies were excluded: one consisted of a selected population (including 14 834 Chinese women with hypertension) and the other two had been carried out in 1992 and between 1992 and 1997 respectively. A recent French study provided insufficient information.…”
Section: Resultsmentioning
confidence: 99%
“…Three large studies were excluded: one 33 consisted of a selected population (including 14 834 Chinese women with hypertension) and the other two 34,35 had been carried out in 1992 and between 1992 and 1997 respectively. A recent French study 36 provided insufficient information.…”
Section: Resultsmentioning
confidence: 99%
“…Lindholt et al [ 10 ] estimated ICER to be GBP 6 090 per gained life-year without long-term cost and discounting. The three other studies that used patient-level data (from local cohort studies or case-control studies) estimated ICER to be in the same order of magnitude, and suggested that screening may be cost-effective [ 11 - 13 ].…”
Section: Resultsmentioning
confidence: 99%